The periurban of the Metropolitan Region of Buenos Aires: tension between food sovereignty and the right to the city (Huellas, 2019)
This article aims at highlighting the potential tension between processes associated with prospect food sovereignty and the right to the city. In the case of the Metropolitan Region of Buenos Aires, we assume that these demands are interwoven in bids for land uses in periurban areas, characterized by a great complexity and overlap of activities. From 1970 onwards, the Metropolitan Region of Buenos Aires has undergone transformations that resulted in processes of exclusion of vulnerable sectors without access to the land. The social production of habitat, as a constituent process of the right to the city, expands into interstices which have not yet been urbanized, overlapping spaces in which activities linked to the production of fresh food that caters to urban markets are carried out, and that in recent years have been recognized in their role to satisfy the food sovereignty of the population. This work aims at providing elements to reflect on the connection between food sovereignty and the right to the city. It results from bibliographical reviews on the subject and arises from interviews conducted in the periurban of the Metropolitan Region of Buenos Aires. The conclusions suggest a tense coexistence between excluded sectors in the periurban and the need to implement measures on land distribution.
Keywords: Periurban; Food Sovereignty; Right to the City